Hard coat film and curable composition
Patent Information
- Application Number
- JP2023138731
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2036-10-31
AI Technical Summary
【0029】 本発明によれば、アンチニュートンリング性、透明性に優れ、ギラツキを低減したハードコートフィルムが提供される。
Smart Images

Figure 0007632540000010 
Figure 0007632540000001 
Figure 0007632540000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a hard coat film having excellent anti-Newton ring properties and transparency and reduced glare, and a curable composition. [Background technology]
[0002] Plastic products, for example, resin substrates such as styrene-based resins such as polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polybutylene terephthalate, ABS, MS resin, and AS resin, vinyl chloride-based resins, and cellulose acetate such as triacetyl cellulose, are particularly excellent in terms of light weight, ease of processability, impact resistance, and the like, and are therefore used in a variety of applications, including as containers, instrument panels, packaging materials, various housing materials, optical disc substrates, plastic lenses, and substrates for display devices such as liquid crystal displays and plasma displays.
[0003] These plastic products have low surface hardness and are easily scratched, and in the case of transparent resins such as polycarbonate and polyethylene terephthalate, the inherent transparency or appearance of the resin is significantly impaired, making it difficult to use plastic products in fields that require abrasion resistance. For this reason, active energy ray-curable hard coat materials (coating materials) are used to impart abrasion resistance to the surfaces of these plastic products.
[0004] In recent years, transparent resin films coated with a hard coat have been widely used in image display devices such as touch panels. In resistive touch panels, an optical pattern called Newton rings occurs when the upper electrode film and the lower electrode substrate come close to each other during input by pressing the panel, causing interference between the reflected lights.
[0005] A representative method for preventing such Newton rings is known to suppress the interference of reflected light by providing irregularities on the surface of the upper electrode. For example, in Patent Document 1, silica particles are blended to form the irregularities. In Patent Document 2, organic fine particles are blended to form the irregularities. On the other hand, in Patent Document 3, the irregularities are formed by phase separation between a multifunctional acrylate with different compatibility and an acrylic polymer with a small solubility parameter. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2002-373056 A [Patent Document 2] JP 2003-191393 A [Patent Document 3] JP 2009-123685 A Summary of the Invention [Problem to be solved by the invention]
[0007] In the above Patent Document 1, the high hardness of the silica particles may damage the lower electrode, resulting in a decrease in durability. In contrast, in the above Patent Document 2, although the organic fine particles prevent the lower electrode from being damaged, there is a problem that the particles are detached and the anti-Newton ring properties are reduced. Furthermore, in the above Patent Document 3, the viscosity adjustment range of the multifunctional acrylate is narrow, making it difficult to achieve sufficiently good transparency.
[0008] The present invention aims to solve the above-mentioned various problems. That is, the object of the present invention is to provide a hard coat film having excellent anti-Newton ring properties and transparency and reduced glare, and a curable composition therefor. [Means for solving the problem]
[0009] The present inventors have conducted intensive research to solve the above problems, and have found that the above problems can be solved by a hard coat film having a surface unevenness structure obtained by curing a curable composition containing a polymer (A) containing a specific high SP value amide group and an unsaturated double bond, a specific low SP value polymer (B) and a polyfunctional (meth)acrylate (C) in a specified ratio, in which the recesses are composed of domains derived from the polymer (A) and the protrusions are composed of domains containing the polymer (B) and derived from the polyfunctional (meth)acrylate (C). That is, the gist of the present invention is as follows.
[0010] [1] A hard coat film having a concave-convex structure on its surface, the concave portions being composed of domains derived from a polymer (A) containing an amide group and an unsaturated double bond and having a solubility parameter (SP value) of 16 to 20, and the convex portions being composed of domains derived from a polymer (B) containing a solubility parameter (SP value) of 10 to 15 and a polyfunctional (meth)acrylate (C) having an SP value of 10 to 15.
[0011] [2] The hard coat film according to [1], which has a surface roughness (Ra) of 0.05 to 1.5 μm as measured by a white light interference microscope.
[0012] [3] The hard coat film according to [1] or [2], which is a cured product of a curable composition containing a polymer (A), a polymer (B), and a polyfunctional (meth)acrylate (C), in which the ratio of [weight of polymer (A)]:[total weight of polymer (B) and polyfunctional (meth)acrylate (C)] is 10:90 to 80:20.
[0013] [4] The hard coat film according to [3], wherein the ratio of [weight of the polymer (B)]:[weight of the polyfunctional (meth)acrylate (C)] in the curable composition is 5:95 to 40:60.
[0014] [5] The hard coat film according to any one of [1] to [4], wherein the viscosity of the polymer (A) measured at 25°C and at a concentration of 30% by weight in propylene glycol monomethyl ether is 100 to 4,000 mPa s.
[0015] [6] The hard coat film according to any one of [1] to [5], wherein the polymer (A) has an unsaturated double bond content of 1.00 to 10.00 mmol / g.
[0016] [7] The hard coat film according to any one of [1] to [6], wherein the polymer (A) has a (meth)acryloyl group.
[0017] [8] The hard coat film according to any one of [1] to [7], wherein the polymer (B) is a (meth)acrylic polymer.
[0018] [9] The hard coat film according to any one of [1] to [8], wherein the polymer (A) has a structural unit derived from a (meth)acrylamide monomer.
[0019]
[10] The hard coat film according to any one of [1] to [9], wherein the polymer (A) has a side chain of a structural unit represented by the following formula (1): [ka] (In formula (1), R represents the main chain portion of the polymer (A), and R 1 represents a hydrogen atom or a methyl group.
[0020]
[11] The hard coat film according to any one of [1] to
[10] , which has a thickness of 1 to 10 μm.
[0021]
[12] A curable composition comprising a polymer (A) having an amide group and an unsaturated double bond, and having a solubility parameter (SP value) of 16 to 20, a polymer (B) having a solubility parameter (SP value) of 10 to 15, and a polyfunctional (meth)acrylate (C) having an SP value of 10 to 15, wherein the ratio of [weight of polymer (A)]:[total weight of polymer (B) and weight of polyfunctional (meth)acrylate (C)] is 10:90 to 80:20.
[0022]
[13] The curable composition according to
[12] , wherein the ratio of [the weight of the polymer (B)]:[the weight of the polyfunctional (meth)acrylate (C)] is 5:95 to 40:60.
[0023]
[14] The curable composition according to
[12] or
[13] , wherein the viscosity of the polymer (A) measured at 25°C and at a concentration of 30% by weight in propylene glycol monomethyl ether is 100 to 4,000 mPa s.
[0024]
[15] The curable composition according to any one of
[12] to
[14] , wherein the polymer (A) has an unsaturated double bond content of 1.00 to 10.00 mmol / g.
[0025]
[16] The curable composition according to any one of
[12] to
[15] , wherein the polymer (A) has a (meth)acryloyl group.
[0026]
[17] The curable composition according to any one of
[12] to
[16] , wherein the polymer (B) is a (meth)acrylic polymer.
[0027]
[18] The curable composition according to any one of
[12] to
[17] , wherein the polymer (A) has a structural unit derived from a (meth)acrylamide monomer.
[0028]
[19] The curable composition according to any one of
[12] to
[18] , wherein the polymer (A) has a side chain of a structural unit represented by the following formula (1): [ka] (In formula (1), R represents the main chain portion of the polymer (A), and R 1 represents a hydrogen atom or a methyl group. Effect of the Invention
[0029] According to the present invention, there is provided a hard coat film which is excellent in anti-Newton ring properties and transparency and reduces glare. [Brief description of the drawings]
[0030] [Figure 1] FIG. 2 is a diagram showing the results of Raman mapping of the hard coat film formed in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The present invention will be described in detail below. However, the following description is an example of an embodiment of the present invention, and the present invention is not limited to the contents of the following description as long as it does not go beyond the gist of the present invention. The present invention can be modified and implemented as desired without departing from the gist of the present invention.
[0032] In the present invention, "(meth)acrylate" is a general term for acrylate and methacrylate, and means either one or both. Similarly, "(meth)acrylic acid" is a general term for acrylic acid and methacrylic acid, and means either one or both, and "(meth)acryloyl group" is a general term for acryloyl group and methacryloyl group, and means either one or both. The same applies to "(meth)acrylamide-based monomer". In the present invention, the weight average molecular weight (Mw) of the polymers (A) and (B) can be determined as a polystyrene standard converted value using GPC (gel permeation chromatography). A specific method for measuring the weight average molecular weight will be described in the Examples section below. The viscosity of the polymer (A) and the polymer (B) can be measured using an E-type viscometer under the following measurement conditions, but for commercially available products, catalog values can be used. <Viscosity measurement conditions> Solid content: 30% by weight Temperature: 25℃ Equipment: TOKIMEC E-type viscometer TV-20
[0033] The hard coat film of the present invention is a hard coat film having an uneven structure on the surface, in which the recesses are composed of domains derived from a polymer (A) containing an amide group and an unsaturated double bond and having a solubility parameter (SP value) of 16 to 20, and the protrusions are composed of domains containing a polymer (B) having a solubility parameter (SP value) of 10 to 15 and derived from a multifunctional acrylate (C) having an SP value of 10 to 15. As described above, the hard coat film of the present invention has recesses and protrusions each composed of a specific domain, and the composition of each domain can be confirmed, for example, by microscopic Raman spectroscopy, as shown in the examples described later.
[0034] [Reasons why the present invention is effective] The hard coat film of the present invention has excellent anti-Newton ring properties, transparency, etc., and further has the effect of reducing glare. The reason why the hard coat film of the present invention has such effects is not clear, but is presumed to be due to the following reasons.
[0035] First, the curable composition of the present invention described later contains a polymer (A), a polymer (B) and a polyfunctional (meth)acrylate (C), and since each of these components has a specific solubility parameter (SP value), when the curable composition is applied to a substrate and irradiated with ultraviolet light or the like, phase separation occurs prior to the curing reaction into the polymer (A) having a higher SP value and the polymer (B) and polyfunctional (meth)acrylate (C) having a lower SP value. As the curing reaction progresses, a recessed portion composed of a domain derived from the polymer (A) and a protruding portion composed of a domain containing the polymer (B) and derived from the polyfunctional (meth)acrylate (C) are formed.
[0036] Newton rings are interference fringes that occur when the surface of a hard coat film is pressed with a finger or the like, due to interference between light reflected from the hard coat film surface and light reflected from the substrate surface. However, since the hard coat film of the present invention has an uneven structure as described above, it is believed that interference between light reflected from the hard coat film surface and light reflected from the substrate surface is suppressed, thereby making it possible to suppress the occurrence of Newton rings (obtain anti-Newton ring properties).
[0037] In high-definition display devices with fine pixel sizes, glare causes degradation of image quality, such as glare on the screen and blurred characters, when the surface irregularities are of a conventional size. That is, in the case of high-definition display devices, the surface irregularities of the conventional size are close to the pixel size of high-definition displays in terms of order, and glare occurs due to the lens effect of the surface irregularities. As will be described in detail later, the hard coat film of the present invention is thought to be able to reduce glare because the shape of the surface irregularities is controlled so as not to be spherical as in the conventional case.
[0038] The hard coat film of the present invention can further have excellent transparency (light transmittance, haze) since the refractive index of the domains derived from the polymer (A) constituting the recesses is close to the refractive index of the domains derived from the polymer (B) and the polyfunctional (meth)acrylate (C) constituting the protrusions.
[0039] [SP value] The solubility parameter (SP value) is a measure of solubility. The larger the SP value, the higher the polarity, and conversely, the smaller the SP value, the lower the polarity. In the present invention, the SP value is a value actually measured by the following method. Weigh 0.5 g of sample into a 100 ml Erlenmeyer flask, add 10 ml of acetone to dissolve the resin. While stirring with a magnetic stirrer, add hexane dropwise to determine the amount of hexane added (vh) at which the solution becomes cloudy (cloudy point). Next, determine the amount of deionized water added (vd) at the cloudy point when deionized water is used instead of hexane. From vh and vd, the SP value can be calculated using the formula given in Reference: SUH, CLARKE, JPSA-1, 5, 1671-1681 (1967). In addition, if the solubility parameter cannot be calculated by the above method, such as when the sample does not dissolve in acetone, it can be estimated by the method proposed by Fedors et al. Specifically, it can be calculated by referring to "POLYMER ENGINEERING AND SCIENCE, FEBRUARY, 1974, Vol. 14, No. 2, ROBERT F. FEDORS. (pages 147-154)".
[0040] [Curable composition] Specifically, the hard coat film of the present invention can be produced by curing the curable composition of the present invention, which contains the above-mentioned polymer (A), polymer (B), and polyfunctional (meth)acrylate (C), and in which the ratio of [weight of polymer (A)]:[total weight of polymer (B) and polyfunctional (meth)acrylate (C)] is 10:90 to 80:20.
[0041] In addition, in the curable composition of the present invention, [weight of polymer (A)]: [total weight of polymer (B) and polyfunctional (meth)acrylate (C)] is preferably 12:88 to 60:40, more preferably 14:86 to 45 to 55, particularly preferably 16:84 to 40:60, and most preferably 20:80 to 35:65. When the blending amounts of polymer (A), polymer (B), and polyfunctional (meth)acrylate (C) are within the above ranges, it is preferable from the viewpoint of improving anti-Newton ring properties, transparency, glare, etc. Furthermore, from the viewpoint of improving these effects, [weight of polymer (B)]: [weight of polyfunctional (meth)acrylate (C)] is preferably 5:95 to 40:60, more preferably 10:90 to 35:65, and most preferably 20:80 to 30:70.
[0042] The hard coat film of the present invention will be described in detail below according to a method for producing the hard coat film of the present invention by curing the curable composition of the present invention. However, the method for producing the hard coat film of the present invention is not limited to the following method.
[0043] <Polymer (A)> The polymer (A) has an SP value of 16 to 20 and contains an amide group and an unsaturated double bond.
[0044] When the curable composition is cured, the polymer (A) undergoes phase separation between the polymer (B) and the functional (meth)acrylate (C) to form domains of recesses and domains of protrusions, so that the SP value of the polymer (A) must be at least 16. When the SP value of the polymer (A) is at most 20, the curable composition has good coatability and good anti-Newton ring properties. The SP value of the polymer (A) is particularly preferably from 17 to 19.8, more preferably from 17.5 to 19.6, and most preferably from 18 to 19.4.
[0045] The polymer (A) is not particularly limited as long as it contains an amide group and an unsaturated double bond, but the polymer (A) preferably contains a (meth)acryloyl group from the viewpoint of UV curability, and preferably contains an amide group from the viewpoint of reducing glare. Moreover, it is preferable that the amide group is contained in the polymer (A) as a structural unit derived from a (meth)acrylamide monomer from the viewpoint of improving the SP value.
[0046] Moreover, it is preferable that the polymer (A) has a side chain of a structural unit represented by the following formula (1) from the viewpoints of transparency and UV curability.
[0047] [ka] (In formula (1), R represents the main chain portion of the polymer (A), and R 1 represents a hydrogen atom or a methyl group. represent.)
[0048] Such a polymer (A) can be obtained, for example, by reacting acrylic acid with a glycidyl group portion of a structural unit derived from glycidyl methacrylate in a copolymer of a (meth)acrylamide monomer, which is a (meth)acrylic monomer having an amide group, and glycidyl methacrylate. By appropriately adjusting the constituent components of the (meth)acrylamide monomer and glycidyl methacrylate, a polymer (A) having an SP value in the above range can be obtained.
[0049] Examples of the (meth)acrylamide monomer used in the production of the polymer (A) include acryloylmorpholine, hydroxylmethylacrylamide, hydroxylethylacrylamide, dimethylacrylamide, diethylacrylamide, and N-isopropylacrylamide. In producing the polymer (A), these may be used alone or in combination of two or more.
[0050] The copolymerization ratio of the (meth)acrylamide monomer and glycidyl methacrylate is preferably, by weight, (meth)acrylamide monomer:glycidyl methacrylate=10-90:90-10, more preferably 75-25:75-25, and particularly preferably 60-40:60-40. When the copolymerization ratio of the (meth)acrylamide monomer and glycidyl methacrylate is within the above range, the SP value and refractive index of the polymer (A) become appropriate values, which is preferable.
[0051] The amount of acrylic acid used is preferably 10 to 50 parts by weight, more preferably 15 to 40 parts by weight, and particularly preferably 20 to 30 parts by weight, based on 100 parts by weight of the total of the (meth)acrylamide monomer and glycidyl methacrylate. By using acrylic acid within the above range, double bonds can be effectively introduced into the polymer side chain of the polymer (A), and the transparency is improved, which is preferable from the viewpoint of UV curability.
[0052] The polymer (A) can be produced, for example, as follows using the above-mentioned (meth)acrylamide monomer, glycidyl methacrylate, and acrylic acid.
[0053] Propylene glycol monomethyl ether is added to a separable flask equipped with a thermometer, a stirrer, a reflux condenser, etc. Meanwhile, a monomer solution is prepared by adding glycidyl methacrylate, a (meth)acrylamide monomer such as acryloylmorpholine, propylene glycol monomethyl ether, and 2,2'-azobis(2,4-dimethylvaleronitrile) to a measuring cylinder or the like. Thereafter, the stirrer in the separable flask is started, and then nitrogen gas is introduced into the separable flask and the measuring cylinder.
[0054] Next, the separable flask is immersed in an oil bath and heated to an internal temperature of about 65°C. Next, the monomer solution prepared in the measuring cylinder is pumped into the separable flask using a pump or the like, and added dropwise to carry out radical polymerization. After the dropwise addition is complete, stirring is continued for about 2 hours at an internal temperature of about 65°C, after which 2,2'-azobis(2,4-dimethylvaleronitrile) is added and reacted for about 3 hours, after which 258.8 g of propylene glycol monomethyl ether and p-methoxyphenol are added and heated to about 100°C.
[0055] Next, acrylic acid and triphenylphosphine are added and reacted at about 110° C. for about 6 hours, whereby a polymer (A) having an amide group and an unsaturated double bond can be obtained.
[0056] The weight average molecular weight (Mw) of the polymer (A) thus obtained is preferably 5000 to 100000, more preferably 10000 to 80000, particularly preferably 15000 to 50000, and most preferably 20000 to 40000. When the weight average molecular weight (Mw) of the polymer (A) is equal to or higher than the lower limit, the fluidity of the components forming the domains in the coating film during drying is appropriately reduced, making it possible to adjust the magnitude of phase separation to an appropriate level for suppressing glare, and when it is equal to or lower than the upper limit, the fluidity of the components forming the domains in the coating film during drying is appropriately maintained, and the anti-Newton ring properties are good without impeding the progress of phase separation.
[0057] The viscosity of the polymer (A) measured at 25°C and a concentration of 30% by weight in propylene glycol monomethyl ether is preferably 100 to 4,000 mPa·s, more preferably 500 to 3000 mPa·s, and most preferably 800 to 2000 mPa·s. If the viscosity of the polymer (A) is above the lower limit, the fluidity of the components forming the domains in the coating film during drying is appropriately reduced, making it possible to adjust the magnitude of phase separation to an appropriate level for suppressing glare, and if the viscosity is below the upper limit, the fluidity of the components forming the domains in the coating film during drying is appropriately maintained, and the anti-Newton ring properties are good without impeding the progress of phase separation. The viscosity of the polymer (A) can be adjusted by appropriately adjusting the molecular weight.
[0058] The polymer (A) preferably has an unsaturated double bond content of 1.00 to 10.00 mmol / g, more preferably 1.5 to 4.5 mmol / g, and most preferably 2 to 4 mmol / g. When the unsaturated double bond content of the polymer (A) is equal to or more than the lower limit, the transparency (total light transmittance) and curability of the cured film are good, and when it is equal to or less than the upper limit, the anti-Newton ring properties of the cured film are good.
[0059] The curable composition of the present invention may contain only one type of polymer (A), or may contain two or more types having different monomer compositions, physical properties, and the like.
[0060] <Polymer (B)> The polymer (B) is a polymer having an SP value of 10-15.
[0061] When the SP value of the polymer (B) is 10 or more, the choice of solvents in which it can be dissolved is broadened, and when it is 15 or less, phase separation from the polymer (A) occurs easily, improving the anti-Newton ring property. The SP value of polymer (B) is particularly preferably 11 to 14.5, and more preferably 12 to 14. The difference between the SP value of polymer (B) and the SP value of polymer (A) is preferably about 1 to 9, more preferably about 3 to 8, and most preferably about 4 to 7. If the difference is within this range, phase separation is likely to occur, as described above, and the anti-Newton ring properties are improved.
[0062] The polymer (B) is not particularly limited, but is preferably a (meth)acrylic polymer.
[0063] In the present invention, the term "(meth)acrylic polymer" refers to a polymer synthesized from a raw material containing (meth)acrylic acid and / or a (meth)acrylic acid derivative, and is used to include a polymer obtained by further modifying this polymer. As long as the polymer uses at least one raw material ((meth)acrylate monomer) containing (meth)acrylic acid or a (meth)acrylic acid derivative, the other raw materials are not particularly limited. For example, the polymer may be a copolymer using a known polymerizable monomer such as a hydrocarbon monomer having a vinyl group other than the (meth)acrylate monomer. In addition, the term "(meth)acrylic acid derivative" refers to a compound having a structure similar to that of (meth)acrylic acid, such as a metal salt of (meth)acrylic acid, a (meth)acrylic acid ester, or a (meth)acrylic acid amide.
[0064] Examples of raw material monomers for producing a (meth)acrylic polymer include acrylic acid, methacrylic acid, and alkyl (meth)acrylate monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, stearyl (meth)acrylate, phenoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, methoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, benzyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentenyloxyethyl (meth)acrylate; (meth)acrylate monomers having an oxirane structure, such as glycidyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, and 3,4-epoxycyclohexylmethyl (meth)acrylate; (meth)acrylate monomers having a fluoroalkyl group, such as perfluorohexylethyl (meth)acrylate, 1H,1H,7H-dodecafluoroheptyl (meth)acrylate, and 1H,1H,9H-hexadecafluorononyl (meth)acrylate; (Meth)acrylate monomers having an amino group, such as N,N-diethylaminoethyl (meth)acrylate and N,N-dimethylaminoethyl (meth)acrylate; (meth)acrylate monomers having a hydroxyl group, such as 2-hydroxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, and 1,6-hexanediol mono(meth)acrylate; Furthermore, examples of raw materials other than the (meth)acrylic acid derivatives include hydrocarbon monomers having a vinyl group, such as styrene, p-chlorostyrene, p-methoxystyrene, divinylbenzene, N-vinylpyrrolidone, N-vinylcaprolactam, acrylonitrile, ethylene glycol divinyl ether, pentaerythritol divinyl ether, 1,6-hexanediol divinyl ether, trimethylolpropane divinyl ether, ethylene oxide-modified hydroquinone divinyl ether, ethylene oxide-modified bisphenol A divinyl ether, pentaerythritol trivinyl ether, dipentaerythritol hexavinyl ether, and ditrimethylolpropane polyvinyl ether.
[0065] These may be used alone or in combination of two or more.
[0066] Among these, alkyl (meth)acrylates such as methyl (meth)acrylate and ethyl (meth)acrylate are preferred. By appropriately adjusting the composition of the raw material monomers used in the production of the polymer (B), the SP value of the polymer (B) can be adjusted to fall within the above range.
[0067] The polymer (B) can be produced by a conventional method, for example, a radical polymerization reaction in which raw material monomers are polymerized in an organic solvent in the presence of a radical polymerization initiator.
[0068] The weight average molecular weight (Mw) of the polymer (B) thus obtained is preferably 50000 to 500000, more preferably 60000 to 300000, even more preferably 65000 to 200000, particularly preferably 70000 to 100000, and most preferably 75000 to 90000. When the weight average molecular weight (Mw) of the polymer (B) is equal to or higher than the lower limit, the fluidity of the components forming the domains in the coating film during drying is appropriately reduced, so that it is possible to adjust the magnitude of phase separation to an appropriate level for suppressing glare. When the weight average molecular weight (Mw) of the polymer (B) is equal to or lower than the upper limit, the fluidity of the components forming the domains in the coating film during drying is appropriately maintained, and the anti-Newton ring properties are improved without impeding the progress of phase separation.
[0069] The viscosity of the polymer (B) measured at 25°C in methyl ethyl ketone at a concentration of 30% by weight is preferably 400 to 2500 mPa·s, more preferably 600 to 2200 mPa·s, and most preferably 800 to 2000 mPa·s. If the viscosity of the polymer (B) is above the lower limit, the fluidity of the components forming the domains in the coating film during drying is appropriately reduced, making it possible to adjust the magnitude of phase separation to an appropriate level for suppressing glare, and if the viscosity is below the upper limit, the fluidity of the components forming the domains in the coating film during drying is appropriately maintained, and the anti-Newton ring properties are improved without impeding the progress of phase separation. The viscosity of the polymer (B) can be adjusted by appropriately adjusting the molecular weight.
[0070] The curable composition of the present invention may contain only one type of polymer (B), or may contain two or more types having different monomer compositions, physical properties, and the like.
[0071] <Polyfunctional (meth)acrylate (C)> The polyfunctional (meth)acrylate (C) is a compound having a (meth)acryloyl group and having two or more unsaturated double bonds in one molecule. For example, such a polyfunctional (meth)acrylate may be a polyfunctional (meth)acrylate having two or more unsaturated double bonds in one molecule, which is a dealcoholization reaction product of a polyhydric alcohol and a (meth)acrylate.
[0072] In the present invention, the polyfunctional (meth)acrylate (C) has an SP value of 10 to 15. When the SP value of the polyfunctional (meth)acrylate (C) is 10 or more, the choice of solvents in which it can be dissolved is broadened, and when the SP value is 15 or less, phase separation with the polymer (A) occurs easily, and the anti-Newton ring property is improved. The SP value of the polyfunctional (meth)acrylate (C) is particularly preferably 11 to 14.5, more preferably 12 to 14. In addition, the difference between the SP value of the polyfunctional (meth)acrylate (C) and the SP value of the polymer (A) is preferably about 1 to 9, more preferably about 3 to 8, and most preferably about 4 to 7. If the difference is within this range, phase separation occurs easily, as described above, and the anti-Newton ring property is improved.
[0073] Of the polyfunctional (meth)acrylates, from the viewpoint of improving the hardness of the obtained hard coat film and the curability of the curable composition, polyfunctional (meth)acrylates having three or more (meth)acryloyl groups in one molecule are preferable, and specific examples thereof include pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate (the SP value of a mixture of pentaerythritol tri(meth)acrylate and pentaerythritol tetra(meth)acrylate is 12.6), dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate (the SP value of a mixture of dipentaerythritol hexa(meth)acrylate and dipentaerythritol penta(meth)acrylate is 12.4), trimethylolpropane tri(meth)acrylate, and the like. Among these, from the viewpoint of obtaining good hardness of the obtained hard coat film and good curability of the curable composition, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and dipentaerythritol penta(meth)acrylate are preferred, and dipentaerythritol hexa(meth)acrylate is particularly preferred.
[0074] The curable composition of the present invention may contain only one type of these polyfunctional (meth)acrylates (C), or may contain two or more types.
[0075] <Compound (D)> The hard coat film of the present invention is preferable because it has a domain derived from a compound (D) having 10 or more carbon atoms and one or more double bonds, which can improve the moist heat resistance. Therefore, similarly, the curable composition of the present invention preferably contains a compound (D) having 10 or more carbon atoms and one or more double bonds. More specifically, the compound (D) is preferably an acrylate having a dimer acid skeleton.
[0076] The lower limit of the number of carbon atoms in the compound (D) is 10 or more, and from the viewpoint of water resistance, it is preferably 14 or more, more preferably 18 or more, and particularly preferably 20 or more. From the viewpoint of crosslinkability and compatibility, the upper limit is preferably 70 or less, more preferably 65 or less, and particularly preferably 60 or less.
[0077] The lower limit of the number of double bonds in compound (D) is 1 or more, preferably 2 or more, and from the viewpoint of water resistance, the upper limit is preferably 5 or less, more preferably 4 or less, and particularly preferably 3 or less.
[0078] Specific examples of the compound (D) include TA37198 and Teslac, both manufactured by Hitachi Chemical.
[0079] The content of the compound (D) in the curable composition of the present invention is preferably 0.1 to 20 parts by weight, more preferably 0.5 to 15 parts by weight, and most preferably 1 to 10 parts by weight, when the total amount of the polymer (A), the polymer (B), and the polyfunctional (meth)acrylate (C) is taken as 100 parts by weight, from the viewpoints of moisture resistance and moist heat resistance.
[0080] <Polymerization initiator> The curable composition of the present invention preferably contains a polymerization initiator in order to cure it with active energy rays. The polymerization initiator can be added in an amount of usually 0.01 parts by weight or more, preferably 0.1 parts by weight or more, more preferably 1 part by weight or more, and usually 20 parts by weight or less, preferably 10 parts by weight or less, based on 100 parts by weight in total of the polymer (A), the polymer (B), the polyfunctional (meth)acrylate (C), and the compound (D) used as needed in the curable composition of the present invention.
[0081] The polymerization initiator is preferably a photopolymerization initiator, and examples thereof include 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2,2-dimethoxy-1,2-diphenylethan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, etc. These polymerization initiators may be used alone or in combination of two or more.
[0082] <Inorganic particles> The curable composition of the present invention may further contain inorganic particles having an average primary particle diameter of 1 μm or less. By containing such inorganic particles, it is possible to provide a hard coat film having good anti-blocking properties while maintaining high hardness.
[0083] That is, by containing the above-mentioned polymer (A) having a high SP value, the polymer (B) having a low SP value, and the polyfunctional (meth)acrylate (C), phase separation can be achieved, and by adding inorganic particles together, when cured, the inorganic particles will be present near the surface together with the phase-separated resin. And, due to the presence of these resins and inorganic particles, appropriate unevenness can be formed on the surface of the hard coat film, and excellent anti-blocking properties can be exhibited.
[0084] Examples of inorganic particles include silica (including organosilica sol), alumina, titania, zeolite, mica, synthetic mica, calcium oxide, zirconium oxide, zinc oxide, magnesium fluoride, smectite, synthetic smectite, vermiculite, ITO (indium oxide / tin oxide), ATO (antimony oxide / tin oxide), tin oxide, indium oxide, antimony oxide, etc., among which silica is preferred. The inorganic particles listed above may be used alone or in combination of two or more.
[0085] The average primary particle size of the inorganic particles is 1 μm or less, preferably 200 nm or less, more preferably 100 nm or less. The lower limit of the average primary particle size of the inorganic particles is not particularly limited, but is usually 5 nm or more, preferably 10 nm or more. If inorganic particles with an average primary particle size of more than 1 μm are used, sedimentation may occur due to the particle's own weight, and the storage stability of the coating liquid of the curable composition may decrease.
[0086] On the other hand, the movement of inorganic particles having an average primary particle size in the above range in the coating liquid of the curable composition is dominated by thermal diffusion rather than gravity-induced sedimentation, so that the inorganic particles can be stably dispersed in the coating liquid of the curable composition, and when a hard coat film is formed, they are effectively present on the surface. Also, the smaller the average primary particle size of the inorganic particles, the better the optical properties tend to be.
[0087] The average primary particle size of the inorganic particles refers to the average value of particle sizes observed with an electron microscope such as a TEM.
[0088] The inorganic particles may be blended in the curable composition of the present invention as inorganic particles surface-modified with a polymer (A) in order to improve antiblocking properties and hardness. For producing inorganic particles surface-modified with a polymer (A), for example, a method of reacting the polymer (A) with inorganic particles in the presence of an acid, a base, or a silane coupling reaction catalyst such as aluminum acetylacetonate at 25 to 120°C for about 1 to 24 hours can be mentioned.
[0089] <Other ingredients> The curable composition of the present invention may contain other components in addition to the above-mentioned polymer (A), polymer (B), polyfunctional (meth)acrylate (C), compound (D), polymerization initiator and inorganic particles, within the scope of not impairing the effects of the present invention. Examples of other components that the curable composition of the present invention may contain include a solvent for uniformly mixing each component, and various commonly used additives such as an antistatic agent, a plasticizer, a surfactant, an antioxidant and an ultraviolet absorber.
[0090] The solvent is not particularly limited, and is appropriately selected in consideration of the polymer (A), the polymer (B), the polyfunctional (meth)acrylate (C), the compound (D) used as needed, the material of the base material serving as the base, the coating method of the composition, and the like. Specific examples of solvents that can be used include aromatic solvents such as toluene and xylene; ketone-based solvents such as methyl ethyl ketone, acetone, methyl isobutyl ketone and cyclohexanone; ether-based solvents such as diethyl ether, isopropyl ether, tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether, anisole and phenetole; ester-based solvents such as ethyl acetate, butyl acetate, isopropyl acetate and ethylene glycol diacetate; amide-based solvents such as dimethylformamide, diethylformamide and N-methylpyrrolidone; cellosolve-based solvents such as methyl cellosolve, ethyl cellosolve and butyl cellosolve; alcohol-based solvents such as methanol, ethanol, propanol, isopropanol and butanol; and halogen-based solvents such as dichloromethane and chloroform.
[0091] These solvents may be used alone or in combination of two or more. Among these solvents, ester-based solvents, ether-based solvents, alcohol-based solvents and ketone-based solvents are preferably used.
[0092] The amount of the solvent used is not particularly limited, and is appropriately determined in consideration of the coatability of the curable composition to be prepared, the viscosity and surface tension of the liquid, the compatibility of the solid content, etc. Usually, the curable composition of the present invention is prepared as a coating liquid having a solid content concentration of 20 to 100% by weight, particularly 30 to 80% by weight, using the above-mentioned solvent. Here, the solid content in the curable composition of the present invention refers to the total of the components other than the solvent contained in the curable composition of the present invention.
[0093] <Method of preparing curable composition> The method for preparing the curable composition of the present invention is not particularly limited, and the composition can be prepared, for example, by mixing the polymer (A), the polymer (B), the polyfunctional (meth)acrylate (C), and, if necessary, the compound (D), a solvent, a polymerization initiator, additives, and the like.
[0094] [Hard-coated films / laminates] The hard coat film of the present invention is obtained by curing the above-mentioned curable composition of the present invention. That is, the hard coat film of the present invention can be obtained by applying the curable composition of the present invention onto a substrate or the like and curing it into a film. In addition, the hard coat film of the present invention can be obtained by applying the curable composition of the present invention onto another resin film as a substrate and curing it to form the hard coat film of the present invention, thereby obtaining a film laminate in which the hard coat film of the present invention is laminated onto the other resin film.
[0095] As the substrate for forming the hard coat film, various resin films and resin plates can be used. As the resin film, for example, triacetyl cellulose (TAC) film, polyethylene terephthalate (PET) film, diacetylene cellulose film, acetate butyrate cellulose film, polyethersulfone film, polyacrylic resin film, polyurethane resin film, polyester film, polycarbonate film, polysulfone film, polyether film, polymethylpentene film, polyetherketone film, (meth)acrylonitrile film, cycloolefin polymer (COP) film, etc. can be used. In addition, as the resin plate, for example, acrylic plate, triacetyl cellulose plate, polyethylene terephthalate plate, diacetylene cellulose plate, acetate butyrate cellulose plate, polyethersulfone plate, polyurethane plate, polyester plate, polycarbonate plate, polysulfone plate, polyether plate, polymethylpentene plate, polyetherketone plate, (meth)acrylonitrile plate, etc. can be mentioned. In addition, glass, etc. can be used as necessary. All of these substrates have excellent transparency and are also preferable for application to the display device described later. The thickness of the substrate can be appropriately selected depending on the application, but generally, a thickness of about 25 to 1000 μm is used.
[0096] The method for applying the curable composition of the present invention is not particularly limited. For example, the composition can be applied by a dip coating method, an air knife coating method, a curtain coating method, a spin coating method, a roller coating method, a bar coating method, a wire bar coating method, a gravure coating method, an extrusion coating method (U.S. Pat. No. 2,681,294), or the like.
[0097] The thickness of the hard coat film of the present invention is not particularly limited and can be appropriately set in consideration of various factors, but is preferably in the range of 1 to 10 μm, particularly 3 to 8 μm, and most preferably 4 to 7 μm.
[0098] The coating film applied and formed on the substrate may be phase-separated at room temperature, or the composition may be dried before curing to cause phase separation in advance. When the applied coating film is dried or heated before curing, it is preferably dried at 30 to 200°C, more preferably 40 to 150°C, for preferably 0.01 to 30 minutes, more preferably 0.1 to 10 minutes, so that the components constituting the recesses and the components constituting the protrusions of the surface unevenness structure of the hard coat film can be phase-separated in advance. Drying before curing to cause phase separation in advance is preferable because it is possible to effectively remove the solvent in the coating film having fine unevenness, and to provide unevenness of the desired size in the hard coat film, which is a cured film.
[0099] As another method for causing phase separation before curing, a method of irradiating the coating film with active energy rays to cause phase separation can also be used. The exposure dose of the active energy rays to be irradiated is, for example, 0.1 to 3.5 J / cm. 2 of light, preferably 0.5 to 1.5 J / cm 2 can be used. The wavelength of the irradiation light is not particularly limited, but for example, irradiation light having a wavelength of 360 nm or less can be used. For example, when 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one or the like is used as the polymerization initiator, the irradiation light is preferably light having a wavelength of about 310 nm or about 360 nm, and more preferably light having a wavelength of about 360 nm. Such light can be obtained using a high pressure mercury lamp, an ultra-high pressure mercury lamp, or the like. By irradiating light in this way, phase separation and curing occur. By irradiating light to cause phase separation, it is preferable because it is possible to avoid unevenness in the surface shape caused by uneven drying of the solvent contained in the curable composition.
[0100] The hard coat film of the present invention having a fine uneven structure on the surface is formed by curing the coating film obtained by coating the curable composition, or the coating film dried after coating. The curing can be carried out by irradiating the coating film with light using a light source that emits active energy rays of a wavelength according to need. The light irradiation for curing is carried out at an integrated light amount of 100 mJ / cm. 2 More than 20,000mJ / cm 2 It is preferable to irradiate so that the following is satisfied: As the light source, a high pressure mercury lamp, an extra high pressure mercury lamp, or the like can be used.
[0101] [Physical Properties] The hard coat film of the present invention provides a favorable unevenness on the surface by phase separation between the component constituting the recesses and the component convexities of the surface unevenness structure of the hard coat film.
[0102] The surface roughness (Ra) of the hard coat film of the present invention measured by a white light interference microscope is preferably 0.05 to 1.5 μm, more preferably 0.1 to 1.2 μm, even more preferably 0.15 to 1.0 μm, particularly preferably 0.2 to 0.85 μm, and most preferably 0.25 to 0.65 μm. By having the surface roughness (Ra) at or above the lower limit, good anti-blocking properties can be obtained. On the other hand, by having the surface roughness (Ra) at or below the upper limit, both low haze and anti-Newton ring properties can be achieved.
[0103] The surface roughness (Rz) of the hard coat film of the present invention measured by a white light interference microscope is preferably 0.05 to 1.5 μm, more preferably 0.1 to 7 μm, even more preferably 0.5 to 5.5 μm, particularly preferably 1 to 5 μm, and most preferably 2 to 4.5 μm. By having the surface roughness (Rz) be equal to or greater than the above lower limit, good anti-blocking properties can be obtained. On the other hand, by having the surface roughness (Rz) be equal to or less than the above upper limit, both low haze and anti-Newton ring properties can be achieved.
[0104] The hard coat film of the present invention also has good hardness. For example, the pencil hardness of a hard coat film formed from the curable composition of the present invention and having a thickness of 3 μm, as measured according to JIS K-5600, is preferably H or more, more preferably 2H or more.
[0105] The hard coat film of the present invention also has good transparency. For example, the hard coat film formed from the curable composition of the present invention and having a thickness of 2 to 3 μm has a total light transmittance of 85% or more, preferably 90% or more, and a haze of 2.0% or less, preferably 1.8% or less, more preferably 1.5% or less, even more preferably less than 1.0%, and particularly preferably less than 0.5%.
[0106] The surface roughness (Ra), surface roughness (Rz), total light transmittance and haze of the hard coat film are measured by the methods described in the Examples section below.
[0107] [Application] The film laminate obtained by laminating the above-mentioned substrate and the hard coat film of the present invention can be used together with a light source to be applied to a display device. In this case, the substrate is preferably a light-transmitting substrate. The light source is preferably disposed on the back surface of the substrate, i.e., on the surface of the substrate opposite to the surface on which the hard coat film is laminated, and irradiates light toward the substrate from there.
[0108] The light source is not particularly limited as long as it can emit light. Examples of the light source include light-emitting diodes, cold cathode fluorescent lamps, hot cathode fluorescent lamps, and EL elements. Alternatively, a liquid crystal module, a backlight unit, and the like may be used.
[0109] The liquid crystal module includes the light source, and further has a configuration in which a polarizing plate / liquid crystal cell / polarizing plate are arranged thereon in this order. The liquid crystal cell is not particularly limited as long as it is one that is generally used in liquid crystal display devices. For example, TN (Twisted Nematic) type liquid crystal cell, STN (Super Twisted Nematic) type liquid crystal cell, HAN (Hybrid Alignment Nematic) type liquid crystal cell, IPS (In Plane Switching) type liquid crystal cell, VA (Vertical Alignment) type liquid crystal cell, MVA (Multiple Vertical Alignment) type liquid crystal cell, OCB (Optical Compensated Bend) type liquid crystal cell, etc. can be mentioned. Such a display device may further include a retardation plate, a brightness improvement film, a light guide plate, a light diffusion plate, a light diffusion sheet, a light collecting sheet, a reflector, etc.
[0110] A display device using a film laminate having the hard coat film of the present invention can be applied to flat panel displays such as liquid crystal display devices (liquid crystal displays), LEDs (light emitting diode displays), ELDs (electroluminescence displays), VFDs (fluorescent displays), and PDPs (plasma display panels).
[0111] An application of a display device using a film laminate having the hard coat film of the present invention includes a touch panel, which has a mechanism for operating a device by pressing a display on a screen, and is useful, for example, in bank ATMs, vending machines, personal digital assistants (PDAs), copiers, facsimiles, game machines, guidance display devices installed in facilities such as museums and department stores, car navigation systems, multimedia stations (multifunction terminals installed in convenience stores), mobile phones, and monitor devices for railway cars. EXAMPLES
[0112] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. Note that the values of various manufacturing conditions and evaluation results in the following examples are meant as preferred upper or lower limit values in the embodiments of the present invention, and the preferred range may be a range defined by a combination of the above-mentioned upper or lower limit values and the values of the following examples or values between the examples.
[0113] The weight average molecular weights of the polymers (A-1), (A-2), (a-1) and (a-2) synthesized in the following Synthesis Examples were measured under the following measurement conditions.
[0114] <Conditions for measuring weight average molecular weight (Mw)> Equipment: Tosoh Corporation "HLC-8120GPC" Column: Tosoh Corporation "TSKgel Super H1000+H2000+H3000" Detector: Differential refractive index detector (RI detector / built-in) Solvent: Tetrahydrofuran Temperature: 40℃ Flow rate: 0.5mL / min Injection volume: 10μL Concentration: 0.2% by weight Calibration sample: monodisperse polystyrene Calibration method: Polystyrene equivalent
[0115] The viscosities of the polymer solutions (A-1), (A-2), (a-1), and (a-2) synthesized in the following Synthesis Examples 1 to 4 and the resin solutions (B-1) to (B-6) prepared in the following Preparation Examples 1 to 6 were measured using an E-type viscometer under the following measurement conditions.
[0116] <Viscosity measurement conditions> Solid content: 30% by weight Temperature: 25℃ Equipment: TOKIMEC E-type viscometer TV-20
[0117] The amount of unsaturated double bonds in the polymers (A-1), (A-2), (a-1), and (a-2) was calculated from the amount of monomer used in the reaction. The consumption rate of acrylic acid was calculated by quantifying the amount of unreacted acrylic acid by the following acid-base titration, and the reaction rate was obtained.
[0118] <Titration of acrylic acid with potassium hydroxide solution> 0.5 g of the reaction solution was dispensed into an Erlenmeyer flask and diluted to 10 g with propylene glycol monomethyl ether solution. To this solution, about 0.1 g of phenolphthalein in ethanol (10%) was added as an indicator, and 0.1 N ethanolic potassium hydroxide solution (manufactured by Wako Pure Chemical Industries, Ltd.) was added dropwise until the solution turned red. The amount of unreacted acrylic acid was determined from the amount added.
[0119] The SP value of each resin was measured by the method described above.
[0120] [Synthesis Example 1: Synthesis of polymer (A-1) containing amide group and unsaturated double bond] To a 2000 mL separable flask equipped with a thermometer, a stirrer and a reflux condenser, 359.6 g of propylene glycol monomethyl ether was added. Meanwhile, 180.0 g of glycidyl methacrylate, 180.0 g of acryloylmorpholine, 180.0 g of propylene glycol monomethyl ether, and 1.80 g of 2,2'-azobis(2,4-dimethylvaleronitrile) were added to a 1000 mL measuring cylinder to prepare a monomer solution. Thereafter, the stirrer of the separable flask was started, and then nitrogen gas was introduced into the separable flask and the measuring cylinder at a flow rate of 300 mL / min for about 1 hour.
[0121] Next, the separable flask was immersed in an oil bath and heated to an internal temperature of 65°C. Next, the monomer solution prepared in the measuring cylinder was pumped into the separable flask and dropped over 2 hours to carry out radical polymerization. After completion of the dropwise addition, stirring was continued for another 2 hours at an internal temperature of 65°C, after which 0.9 g of 2,2'-azobis(2,4-dimethylvaleronitrile) was added and reacted for 3 hours, after which 258.8 g of propylene glycol monomethyl ether and 1.55 g of p-methoxyphenol were added and heated to 100°C.
[0122] Next, 93.07 g of acrylic acid and 6.80 g of triphenylphosphine were added and reacted at 110°C for 6 hours to obtain a (meth)acryloyl copolymer (A-1) having an amide group and an unsaturated double bond and an unsaturated double bond amount (acryloyl equivalent (amount of acryloyl group introduced)) of 2.82 mmol / g. The resulting (meth)acryloyl copolymer (A-1) had an SP value of 19.1 and an acrylic acid consumption rate of 93%. The viscosity of this solution (solid content 30% by weight) at 25° C. was 1,050 mPa·s. The weight average molecular weight (Mw) of the (meth)acryloyl copolymer (A-1) was 22,500.
[0123] [Synthesis Example 2: Synthesis of polymer (A-2) containing amide group and unsaturated double bond] To a 2000 mL separable flask equipped with a thermometer, a stirrer and a reflux condenser, 359.6 g of propylene glycol monomethyl ether was added. Meanwhile, a monomer solution was prepared by adding 180.0 g of glycidyl methacrylate, 180.0 g of acryloylmorpholine, 180.0 g of propylene glycol monomethyl ether, 1.80 g of 2,2'-azobis(2,4-dimethylvaleronitrile), and 7.2 g of γ-trimethoxysilylpropanethiol (KBM-803, manufactured by Shin-Etsu Chemical Co., Ltd.) to a 1000 mL measuring cylinder. Thereafter, the stirrer of the separable flask was started, and then nitrogen gas was introduced into the separable flask and the measuring cylinder at a flow rate of 300 mL / min for about 1 hour.
[0124] Next, the separable flask was immersed in an oil bath and heated to an internal temperature of 65°C. Next, the monomer solution prepared in the measuring cylinder was pumped into the separable flask and dropped over 2 hours to carry out radical polymerization. After completion of the dropwise addition, stirring was continued for another 2 hours at an internal temperature of 65°C, after which 0.9 g of 2,2'-azobis(2,4-dimethylvaleronitrile) was added and reacted for 3 hours, after which 258.8 g of propylene glycol monomethyl ether and 1.55 g of p-methoxyphenol were added and heated to 100°C.
[0125] Next, 93.07 g of acrylic acid and 6.80 g of triphenylphosphine were added and reacted at 110°C for 6 hours to obtain a (meth)acryloyl copolymer (A-2) having an amide group and an unsaturated double bond and an unsaturated double bond amount of 2.81 mmol / g.
[0126] The resulting (meth)acryloyl copolymer (A-2) had an SP value of 19.1 and an acrylic acid consumption rate of 93%. The viscosity of this solution (solid content 30% by weight) at 25° C. was 220 mPa·s. The weight average molecular weight (Mw) of the (meth)acryloyl copolymer (A-2) was 10,080.
[0127] [Synthesis Example 3: Synthesis of polymer (a-1) (for comparison) containing no amide group but containing unsaturated double bonds] Into a flask equipped with a thermometer, a stirrer, and a reflux condenser, 157.3 g of propylene glycol monomethyl ether, 98.0 g of glycidyl methacrylate, 1.0 g of methyl methacrylate, 1.0 g of ethyl acrylate, 1.9 g of mercaptopropyltrimethoxysilane, 1.0 g of 2,2'-azobis(2,4-dimethylvaleronitrile), and 1.9 g of γ-trimethoxysilylpropanethiol (KBM-803, manufactured by Shin-Etsu Chemical Co., Ltd.) were added, and the mixture was reacted at 65°C for 3 hours. Then, 0.5 g of 2,2'-azobis(2,4-dimethylvaleronitrile) was further added and reacted for 3 hours, after which 138.1 g of propylene glycol monomethyl ether and 0.45 g of p-methoxyphenol were added and heated to 100°C. Next, 50.7 g of acrylic acid and 3.08 g of triphenylphosphine were added and reacted at 110° C. for 6 hours to obtain a (meth)acryloyl copolymer (a-1) having an unsaturated double bond amount of 4.62 mmol / g.
[0128] The resulting (meth)acryloyl copolymer (a-1) had an SP value of 17.4 and an acrylic acid consumption rate of 94%. The viscosity of this solution (solid content 30% by weight) at 25° C. was 100 mPa·s. The weight average molecular weight (Mw) of the (meth)acryloyl copolymer (a-1) was 17,700.
[0129] [Synthesis Example 4: Synthesis of polymer (a-2) (for comparison) containing no amide group but containing unsaturated double bonds] Into a flask equipped with a thermometer, a stirrer, and a reflux condenser, 155.1 g of propylene glycol monomethyl ether, 76.0 g of glycidyl methacrylate, 24.0 g of methyl methacrylate, 1.0 g of ethyl acrylate, 1.9 g of mercaptopropyltrimethoxysilane, 1.0 g of 2,2'-azobis(2,4-dimethylvaleronitrile), and 1.9 g of γ-trimethoxysilylpropanethiol (KBM-803, manufactured by Shin-Etsu Chemical Co., Ltd.) were added, and the mixture was reacted at 65°C for 3 hours. Then, 0.5 g of 2,2'-azobis(2,4-dimethylvaleronitrile) was further added and reacted for 3 hours, after which 185.6 g of propylene glycol monomethyl ether and 0.49 g of p-methoxyphenol were added and heated to 100°C. Next, 39.3 g of acrylic acid and 2.82 g of triphenylphosphine were added and reacted at 110° C. for 6 hours to obtain a (meth)acryloyl copolymer (a-2) having an unsaturated double bond amount of 4.59 mmol / g.
[0130] The resulting (meth)acryloyl copolymer (a-2) had an SP value of 17.1 and an acrylic acid consumption rate of 95%. The viscosity of this solution (solid content 30% by weight) at 25° C. was 200 mPa·s. The weight average molecular weight (Mw) of the (meth)acryloyl copolymer (a-2) was 20,700.
[0131] The compositions (parts by weight) of the raw material components used in Synthesis Examples 1 to 4 are summarized in Table 1. In the table, "-" indicates that the component was not used.
[0132] [Table 1]
[0133] [Preparation Example 1: Preparation of resin solution (B-1)] 700g of methyl ethyl ketone was placed in a 2000mL recovery flask and heated to an internal temperature of 80°C. Next, 300g of a (meth)acrylic polymer (Kuraray's methyl methacrylate-methyl acrylate copolymer Parapet HR-L, weight average molecular weight (Mw) 80,700 (measured under the following measurement conditions)) was added little by little and stirred until completely dissolved. The viscosity of this resin solution (solid content 30% by weight) was 1,100mPa·s. The SP value of the (meth)acrylic polymer Parapet HR-L used was 13.5.
[0134] <Conditions for measuring weight average molecular weight> Equipment: Tosoh Corporation "HLC-8120GPC" Column: Tosoh Corporation "TSKgel Super H3000+H4000+H6000" Detector: Differential refractive index detector (RI detector / built-in) Solvent: Tetrahydrofuran Temperature: 40℃ Flow rate: 0.5ml / min Injection volume: 10μL Concentration: 0.2% by weight Calibration sample: monodisperse polystyrene Calibration method: Polystyrene equivalent
[0135] [Preparation Example 2: Preparation of resin solution (B-2)] The same procedure was followed except that the resin used to prepare the resin solution was Mitsubishi Rayon's BR-75 (acrylic copolymer, weight average molecular weight (Mw) 85,000 (catalog value)). The viscosity of this resin solution (solid content 30% by weight) was 470 mPa s. The SP value of the (meth)acrylic polymer BR-75 used was 13.5.
[0136] [Preparation Example 3: Preparation of resin solution (B-3)] The same procedure was repeated except that the resin used to prepare the resin solution was Mitsubishi Rayon's BR-80 (acrylic copolymer, weight average molecular weight (Mw) 95,000 (catalog value)). The viscosity of this resin solution (solid content 30% by weight) was 1,900 mPa s. The SP value of the (meth)acrylic polymer BR-80 used was 13.4.
[0137] [Preparation Example 4: Preparation of resin solution (B-4)] The same procedure was repeated except that the resin used to prepare the resin solution was Mitsubishi Rayon's BR-84 (acrylic copolymer, weight average molecular weight (Mw) 120,000 (catalog value)). The viscosity of this resin solution (solid content 30% by weight) was 1,940 mPa s. The SP value of the (meth)acrylic polymer BR-84 used was 13.6.
[0138] [Preparation Example 5: Preparation of resin solution (B-5)] The same procedure was followed except that the resin used to prepare the resin solution was Mitsubishi Rayon's BR-85 (acrylic copolymer, weight average molecular weight (Mw) 280,000 (catalog value)). The viscosity of this resin solution (solid content 30% by weight) was greater than 50,000 mPa s. The SP value of the (meth)acrylic polymer BR-85 used was 13.5.
[0139] The physical properties of the (meth)acryloyl copolymers (A-1), (A-2), (a-1), (a-2) and the (meth)acrylic polymers of the resin solutions (B-1) to (B-5) are summarized in Table 2. The viscosities of the (meth)acryloyl copolymers (A-1), (A-2), (a-1), and (a-2) are measured at 25°C in 30% by weight propylene glycol monomethyl ether (PGME), and the viscosities of the (meth)acrylic polymers used in the resin solutions (B-1) to (B-5) are measured at 25°C in 30% by weight methyl ethyl ketone (MEK).
[0140] [Table 2]
[0141] [Example 1] <Production of Curable Composition> A glass sample bottle was mixed with 7.32 parts by weight of the (meth)acryloyl copolymer (A-1), 2.05 parts by weight of the resin solution (B-1), and 4.51 parts by weight of dipentaerythritol hexaacrylate (DPHA (SP value: 12.1)) as a multifunctional (meth)acrylate (C-1), and then 0.183 parts by weight of 1-hydroxycyclohexylphenylketone (BASF's "Irgacure (registered trademark) 184") was added as a polymerization initiator, and 15.94 parts by weight of methyl ethyl ketone was further added to obtain a curable composition.
[0142] <Coating process> The obtained curable composition was applied to a transparent biaxially stretched PET film having a thickness of 188 μm (haze value 0.8%; product name: Diafoil (registered trademark) O321E, manufactured by Mitsubishi Plastics, Inc.) using a bar coater so that the coating thickness after drying would be 2 to 3 μm, and the film was dried by heating at 80° C. for 1 minute.
[0143] <Curing process> A PET film with a coating film of the curable composition was irradiated with ultraviolet light using a high-pressure mercury lamp with an output density of 120 W / cm as a light source at a position 15 cm below the light source using "EYE UV METER UVPF-A1, PD365" manufactured by Eye Graphic Co., Ltd. so that the integrated light quantity became 500 mJ / cm 2 to obtain a cured film. The following evaluations were performed on the film laminate with this cured film (hard coat film) formed thereon. The results are shown in Table-3.
[0144] In Table-3, the blending amount of the curable composition is shown as a converted amount when the total of the (meth)acryloyl copolymer (A-1), the (meth)acrylic polymer in the resin solution (B-1), and DPHA (C-1) is 100 parts by weight, and all are blending amounts of pure components. The same applies to Examples 2 to 9 and Comparative Examples 1 to 13 below.
[0145] [Evaluation of Hard Coat Film] <Ra and Rz (Arithmetic Mean Roughness)> The measurement was carried out using a white light interference microscope ("WYKO NP9100" manufactured by Nippon Beechey Co., Ltd.) to determine the arithmetic mean roughness (Ra) and (Rz) in a range of 900 μm × 1300 μm in accordance with JIS B0601-1994 edition. Ra and Rz (JIS B 0601-1994) refer to values obtained by extracting a reference length only in the direction of the mean line from the roughness curve, taking the X-axis in the direction of the mean line of this extracted part and the Y-axis in the direction of the vertical magnification, and expressing the roughness curve as y = f(x), and representing the values obtained by a mathematical formula in micrometers (μm).
[0146] <Total Light Transmittance · Haze> The total light transmittance (Tt (%)) of the hard coat film was measured by measuring the incident light intensity (T0) on the hard coat film and the total transmitted light intensity (T1) transmitted through the hard coat film, and calculated by the following formula. Tt (%) = (T1 / T0) × 100 The total light transmittance can be measured using, for example, a haze meter ("SH7000" manufactured by Nippon Denshoku Industries Co., Ltd.). The haze of the hard coat film was calculated from the following formula in accordance with JIS K-7136 (2000). H(%)=(Td / Tt)×100 H: Haze (%) Td: Diffuse transmittance (%) Tt: Total light transmittance (%)
[0147] <Glare> The obtained film laminate was placed on a liquid crystal display of about 123 dpi (diagonal 10.4 inches, XGA (1,024 x 768 dots)) and the presence or absence of glare was visually confirmed. Those with absolutely no noticeable glare were rated as excellent (◎), those with no noticeable glare but inferior to those of ◎ were rated as good (○), those with only a faint glare were rated as somewhat good (△), and those with clearly noticeable glare were rated as poor (×).
[0148] <Anti-Newton Ring (ANR) properties> A 5 mm thick glass plate was placed on the hard-coated film of the film laminate so that the glass plate and the hard-coated film were in contact with each other. The hard-coated film was then pressed against the glass plate, and the presence or absence of Newton's rings was visually observed from a 60 degree diagonal direction in the area where the hard-coated film and the glass plate were in contact. Those in which no Newton's rings were visible were rated as excellent (◎), those in which no Newton's rings were visible but inferior to ◎ were rated as good (○), those in which the Newton's rings were faintly visible were rated as fair (△), and those in which the rings were clearly visible were rated as poor (×).
[0149] <Microscopic Raman spectroscopy> A confocal Raman microscope spectrometer (Nanophoton Raman Touch) was used to perform Raman spectroscopy of the hard coat film. Excitation light was 532 nm (laser output: 0.1 mW or less), which was introduced into the microscope and focused on the sample by an objective lens. Backscattering from the sample was collected by the same objective lens and passed through a pinhole to obtain the confocal effect. Rayleigh scattered light was removed by a notch filter, and the light was introduced into a spectrometer (diffraction grating: 300 grooves / mm), and the Raman spectrum was obtained by a CCD camera.
[0150] In the above Raman spectroscopy measurement, the piezo stage was moved with an exposure time of 10 s at each point, and the Raman spectrum at each point was obtained and Raman mapping was performed. -1 The Raman band with a peak at 950 to 1050 cm was used as an index for the multifunctional (meth)acrylate (C-1) and was set as the reference peak. -1 The Raman band with a peak at 800-850 cm is the index of the (meth)acryloyl copolymer (A-1). -1 The Raman band with the peak at the peak was used as an index for polymer (B)-1. The results of Raman mapping based on the respective peak intensities are shown in FIG.
[0151] FIG. 1 shows that the recesses of the hard coat film are mainly composed of domains of the (meth)acryloyl copolymer (A-1), and the protrusions are mainly composed of domains of the resin (B-1) and the polyfunctional (meth)acrylate (C-1).
[0152] [Examples 2 to 9, Comparative Examples 1 to 13] A hard coat film was obtained in the same manner as in Example 1, except that the formulation of the curable composition was changed as shown in Tables 3 and 4. Ra, Rz, total light transmittance, haze, glare, and ANR were evaluated in the same manner as in Example 1, and the results are shown in Tables 3 and 4. In Tables 3 and 4, "polymer (A)", "polymer (B)", and "polyfunctional (meth)acrylate (C)" are respectively described as "component (A)", "component (B)", and "component (C)".
[0153] [Table 3]
[0154] [Table 4]
[0155] From Tables 3 and 4, it can be seen that the hard coat film of the present invention using components (A), (B) and (C) has excellent anti-Newton ring properties and transparency, and is free from the problem of glare.
Claims
1. A hard coat film having an uneven surface structure. the recess is constituted by a domain derived from a polymer (A) containing an amide group and an unsaturated double bond and having a solubility parameter (SP value) of 18 to 19.4; The convex portion includes a polymer (B) having a solubility parameter (SP value) of 12 to 14, and is composed of a domain derived from a polyfunctional (meth)acrylate (C) having an SP value of 12 to 14. A hard coat film, The surface roughness (Ra) measured by a white light interference microscope is 0.25 to 1.2 μm; a cured product of a curable composition comprising a polymer (A), a polymer (B), and a polyfunctional (meth)acrylate (C), in which the ratio of [weight of polymer (A)]:[total weight of polymer (B) and polyfunctional (meth)acrylate (C)] is 20:80 to 35:65 and the ratio of [weight of polymer (B)]:[weight of polyfunctional (meth)acrylate (C)] is 10:90 to 35:65, The amount of unsaturated double bonds in the polymer (A) is 2 to 4 mmol / g, The polymer (B) is a (meth)acrylic polymer, A hard coat film, comprising a polymer (A) having a side chain of a structural unit represented by the following formula (1): 【Chemistry 1】 (In formula (1), R represents the main chain portion of the polymer (A), and R 1 represents a hydrogen atom or a methyl group.)
2. 2. The hard coat film according to claim 1, wherein the viscosity of the polymer (A) measured at 25° C. and at a concentration of 30% by weight in propylene glycol monomethyl ether is 100 to 4,000 mPa·s.
3. 3. The hard coat film according to claim 1, which has a thickness of 1 to 10 μm.
4. A curable composition comprising a polymer (A) containing an amide group and an unsaturated double bond and having a solubility parameter (SP value) of 18 to 19.4, a polymer (B) having a solubility parameter (SP value) of 12 to 14, and a polyfunctional (meth)acrylate (C) having an SP value of 12 to 14, wherein the ratio of [weight of polymer (A)]:[total weight of polymer (B) and weight of polyfunctional (meth)acrylate (C)] is 20:80 to 35:65, [the weight of the polymer (B)]:[the weight of the polyfunctional (meth)acrylate (C)] is 10:90 to 35:65, The amount of unsaturated double bonds in the polymer (A) is 2 to 4 mmol / g, The polymer (B) is a (meth)acrylic polymer, A curable composition, wherein the polymer (A) has a side chain of a structural unit represented by the following formula (1): 【Chemistry 2】 (In formula (1), R represents the main chain portion of the polymer (A), and R 1 represents a hydrogen atom or a methyl group.)
5. The curable composition according to claim 4, wherein the viscosity of the polymer (A) measured at 25° C. and at a concentration of 30% by weight in propylene glycol monomethyl ether is 100 to 4,000 mPa·s.
Citation Information
Patent Citations
Active energy beam curing type resin composition
JP1990103215A
Active energy ray-curable resin composition, and method for forming film therefrom
JP1998204326A
Newton ring prevention film and touch panel
JP2002373056A
Anti-newtonian ring film
JP2003191393A
Coating liquid for active energy-ray curable inkjet recording material, and method for manufacturing inkjet recording material by using it
JP2007160786A